Characterization of nanocomposite polyvinyl alcohol/cellulose acetate blend gel polymer electrolytes for supercapacitor application - Rahim, A.A.; Shamsuri, N.A.; Adam, A.A.; Aziz, M.F.; Hamsan, M.H.; Rusdi, M.; Jin Siong, Steve Ong; Noor, I.M.; Kadir, M.F.Z.; Shukur, M.F. (Elsevier, 2024)
High ionic conductivity polymer electrolyte has been introduced to replace the liquid electrolyte used in commercial energy storage devices as they have a tendency in leakage. However, the high degree of crystallinity in polymer electrolyte limits further enhancement of ionic conductivity. In this work, a nanocomposite gel polymer electrolyte system comprising polymer blend of polyvinyl alcohol (PVA) – cellulose acetate (CA) with dopant lithium acetate (LiAc) salt in dimethylformamide (DMF) solvent has been prepared using solution casting method. Different concentrations of titanium dioxide (TiO2) nanofiller were added to study the effect of nanofiller on characteristics of the electrolytes. Fourier transform infrared (FTIR) spectroscopy, impedance spectroscopy (EIS), and differential scanning calorimetry (DSC) were used to study the complexation between the materials, ionic conductivity, and thermal properties, respectively. The trend of the FTIR spectrum in the hydroxyl band showed that the lowered shifting wavenumber indicates a decreased crystalline phase with increasing TiO2 concentration. The highest conductivity of (3.30 ± 0.15) Å~ 10−4 S cm−1 at room temperature was obtained with addition of 8 wt% of TiO2. DSC analysis discovered the increase in conductivity is associated with a decrease in the glass transition temperature (Tg). From transport number measurements (TNM), ions have been found to be the dominant charge carriers. Linear sweep voltammetry (LSV) result indicated that the most conducting electrolyte was electrochemically stable up to 2.2 V. The highest conducting electrolyte was used in the application of an electrochemical double layer capacitor (EDLC). The performance of the EDLC was characterized by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) techniques. Specific capacitance (Csp) of the electrode obtained from CV was 26.23 F g−1 at 5 mV s−1 scan rate. The EDLC had been charged and discharged for 4600 cycles with the highest single electrode specific discharge capacitance (Cd) value of 18.01 F g−1.